Degree Of Uterine Leiomyoma Volume Shrinkage After Transcatheter Embolization In Symptomatic Uterine Leiomyomas (Journal of Pharmaceutical Negative Results, 2023)
Background Uterine artery embolization (UAE) has been proven to be an effective and safe method with a relatively high success rate in minimizing pain, bulk symptoms and bleeding linked to uterine leiomyoma. Uterine artery embolization is increasingly being preferred over surgical hysterectomy or myomectomy due to reduced morbidity, shorter hospitalization and relative uterine preservation when compared to surgical resolution. Material and methods Our study protocol was approved by the institutional review board, and informed consent was obtained. The study was done between January 2020 and June 2021, 23 women scheduled for UAE for symptomatic uterine fibroids (median age, 37 years; range, 28-49 years) was included in our study. Pelvic MRI was performed before and 6 months after uterine artery embolization. Uterine leiomyoma shrinkage volume concluded from pre and post-procedure MRI scans. Results Our study showed that the dominant fibroid volume significantly decreased from median 125 cm3 to 43 cm3 with percentage of fibroid reduction about 63.0% 6 months after embolization. As regarding uterine volume, it was decreased from 1020.65±359.86 cm3 to 681.17±218.79 cm3 with 33.2% percentage of uterine reduction 6 months follow up after embolization. Also, there was significant improvement in presenting symptoms of patients including heavy bleeding, pelvic pain and pressure symptoms. Conclusion Uterine artery embolization is a safe and effective treatment choice for patients with symptomatic fibroids. UAE could significantly reduce the fibroid size as well as the mean menstrual duration and amount.